hubungan dukungan orang dengan minat berwirausaha lulusan pelatihan kue balai latihan kerja batusangkar - Ismaniar, Ismaniar; Annisa, Adhira Defri (Universitas Negeri Padang, 2024)
ABSTRACT This research was motivated by the low level of this problem because many of the training graduates lacked capital to start a business and lacked support from family in opening their own cake making business and of course had to rely on parental support: 1). Support from parents of cake making training graduates at the Batusangkar Job Training Center is categorized as quite low 2). Entrepreneurial interest of cake training graduates at the Batusangkar Job Training Center is categorized as low. 3). There is a significant relationship between parental support and entrepreneurial interest of cake making graduates at the Batusangkar Job Training Center. It is recommended: 1.) for parents to support their children's interests and talents by providing a platform for developing the skills they have acquired during training so that they can be implemented and are useful for themselves and others. 2.) Institutions can work together with parents to help foster interest in entrepreneurship in training graduates so they can apply the skills they have acquired during the training. 3.) For future researchers, they can conduct research on other variables related to interest in entrepreneurship Keywords: Parental Support, Entrepreneurship